Local Government Unit Initiative on Implementing Marine Protected Areas in Barangay Kamanga and Colon, Maasim Sarangani Province - Jama, Ryan; Flores, Leonard (Journal of Interdisciplinary Perspectives, 2024)
This study assessed local government unit initiatives in implementing Marine Protected Areas (MPAs) in Maasim, Sarangani Province. The evaluation focused on the effectiveness of MPA program implementers using the Management Effectiveness Assessment Tool (MEAT), collected secondary data on coral reefs and reef fish conditions, conducted a community perception survey, and assessed socioeconomic impacts. Despite the establishment of MPAs and the adoption of related policies, knowledge gaps persist regarding their actual effectiveness in achieving conservation objectives. This study evaluated the management performance of two MPAs: Kamanga Marine Ecotourism Park and Sanctuary and Colon Marine Sanctuary. Employing a descriptive design, MEAT was used to assess their effectiveness. Results indicate that both MPAs were well-established, with robust stakeholder involvement and legal enforcement. However, Kamanga Marine Ecotourism Park and Sanctuary outperformed Colon Marine Sanctuary in areas such as patrolling, infrastructure, institutional support, and impact assessment. Kamanga Marine Ecotourism Park and Sanctuary received an "excellent" rating, while Colon Marine Sanctuary was rated "very good." Both MPAs have stable funding, but Colon Marine Sanctuary requires monitoring, communication, public engagement, and financial management improvements. The study also identified challenges from natural factors and human activities, including pollution and fishing. However, there is positive community awareness about MPAs, and fishers report benefits such as increased fish stocks.